HUBUNGAN VERBAL BULLYING TERHADAP KECERDASAN INTERPERSONAL SISWA SDN 101744 HAMPARAN PERAK - Vinna Agusrian; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2023)
Lack of student interpersonal intelligence can cause a person to behave in a socially deviant manner. As a result of low interpersonal intelligence can cause children to do verbal bullying. This study aims to determine the relationship between verbal bullying and interpersonal intelligence of fourth grade students at SD 10174 Hamparan Perak in the academic year 2022/2023. This type of research is correlational. The sample in this study was class IV B as many as 26. The instrument in this study was a questionnaire in the form of a Likert scale. Ui instrument and test requirements analysis using SPSS 22.0 for windows program. Hypothesis testing using SPSS 22.0 product moment correlation test for windows. Based on the results of the data analysis of interpersonal intelligence, students are in the high criteria with a frequency of 5 with a percentage of 19.23%, a medium category with a frequency of 18 and a percentage of 69, 23%, and a low category of 3 with a percentage of 11, 53%. The results showed that there was a significant relationship between verbal bullying and the interpersonal intelligence of grade IV B students at SDN 101744 Hamparan Perak. It is evident from the results of the correlation analysis of 69.23%. This means that there can be a negative relationship between verbal bullying and interpersonal intelligence. So it can be concluded that the higher the interpersonal intelligence, the lower the verbal bullying behavior.